In search of the next growth episode: How firms catalyse and sustain periods of high growth. (September 2022) - Raby, Simon; Hart, Mark; Harney, Brian
This is an introductory article to the special issue In Search of the Next Growth Episode: How Firms Catalyse and Sustain Periods of High Growth. The article reviews alternative streams of research on firm growth, including 'random growth', 'responsive growth' and 'resourceful growth'. The themes of, and contributions to, the Special Issue are presented. Finally, we identify a number of directions for future research, including the importance of unpacking the drivers and causes of high growth episodes (HGEs), amplifying the role of the leader in research on firm growth, while questioning the desired outcomes and consequences of growth. We assert that there is still much to learn about firm growth. Our hope is that this special issue inspires new approaches and an enlarged understanding in this domain.